USE OF MEGGER MEASURING TOOLS IN MEASURING THE INSULATION RESISTANCE OF CT CUBICLE 20KV PALIMA REFEITER (ULP SERANG) - Romdoni, Sohip Romdoni; Bagus Dwi Cahyono (Universitas Tarumanagara, 2024)
This study aims to evaluate the effectiveness of the Kyoritsu 3123A Megger (Insulation Tester) in measuring the insulation resistance of 20kV cubicles at the Dukuh Feeder, PT PLN (ULP Serang). PT PLN, as the main national electricity provider, is responsible for maintaining the security and reliability of the distribution network, where the quality of cubicle insulation is very important to prevent current leakage and potential fire risks. The Megger measuring instrument is used to detect insulation conditions on important components such as Current Transformers (CT), producing significant measurements at voltages of 5,000 to 10,000 volts DC. This study uses literature study methods, field observations, and technician interviews to verify the reliability of the tool in practice. Insulation resistance measurements are carried out with standardized procedures, ensuring that there is no active voltage in the cubicle, as well as accurate steps for optimal results. The measurement results show an insulation resistance value of 200 Mega ohms on each phase to ground, indicating that the insulation conditions are within safe limits according to applicable standards. The significance of these results shows that the Kyoritsu 3123A Megger is able to provide accurate and reliable measurements, making it the right solution for early detection of insulation problems and preventive repairs. This evaluation is expected to be a guide for periodic maintenance in the PT PLN distribution system, so that the long-term security and reliability of the electricity network can be maintained and the quality of service to the community remains optimal Abstrak Penelitian ini bertujuan mengevaluasi efektivitas alat ukur Megger (Insulation Tester) tipe Kyoritsu 3123A dalam pengukuran tahanan isolasi pada kubikel 20kV di Penyulang Dukuh, PT PLN (ULP Serang). PT PLN, sebagai penyedia utama listrik nasional, bertanggung jawab menjaga keamanan dan keandalan jaringan distribusi, di mana kualitas isolasi kubikel sangat penting untuk mencegah kebocoran arus serta potensi risiko kebakaran. Alat ukur Megger digunakan dalam mendeteksi kondisi isolasi pada komponen penting seperti Current Transformer (CT), menghasilkan pengukuran signifikan pada tegangan 5.000 hingga 10.000 volt DC. Penelitian ini menggunakan metode studi literatur, observasi lapangan, dan wawancara teknisi untuk memverifikasi keandalan alat dalam praktik. Pengukuran tahanan isolasi dilakukan dengan prosedur terstandar, memastikan tidak ada tegangan aktif pada kubikel, serta langkah-langkah akurat untuk hasil yang optimal. Hasil pengukuran menunjukkan nilai tahanan isolasi sebesar 200 Mega ohm pada setiap fasa terhadap ground, mengindikasikan bahwa kondisi isolasi berada dalam batas aman sesuai standar yang berlaku. Signifikansi hasil ini menunjukkan bahwa alat Megger Kyoritsu 3123A mampu memberikan pengukuran yang akurat dan andal, menjadikannya solusi tepat dalam deteksi dini masalah isolasi dan perbaikan preventif. Evaluasi ini diharapkan dapat menjadi panduan untuk pemeliharaan berkala dalam sistem distribusi PT PLN, sehingga keamanan dan keandalan jangka panjang jaringan listrik dapat terjaga serta kualitas layanan kepada masyarakat tetap optimal.